Application of Aspects of Consent in Medical Procedures (Informed Consent) As a Form of Consensualism Principle - Rika Saraswati; Ch. Retnaningsih; Chaliza Adnan (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: Health is a fundamental and very fundamental thing in human life, health is a blessing given by God to humans, therefore humans must take care, however, humans who have maintained their health will not always be healthy, but there are conditions where humans need help with exercise medical personnel to maintain their health. Medical personnel who are experts in the field of health have an obligation to carry out their duties as guardians of public health. In every action of medical personnel to humans or referred to as patients, there must be consent which is the basic principle of carrying out medical services, therefore in this study the researcher focuses on the application of the aspect of consent in medical actions to patients. This study aims to analyze the aspect of consent in a medical action called informed consent which is based on the principle of agreement adopted by Indonesian positive law. This study uses a normative juridical research method which is a study of regulations and literature related to the problems to be discussed. The results of the study are expected to be a legal reference for the community and also medical personnel so that they can increase understanding and awareness of medical actions that have high risks by upholding their professional code of ethics and carrying out all work procedures in accordance with applicable regulations.Keywords: Consent in a Medical Action, Informed consent, Principle of Consensualism. Abstrak: Kesehatan merupakan hal yang mendasar dan sangat fundamental dalam kehidupan manusia, kesehatan merupakan berkah yang diberikan oleh Tuhan kepada manusia, oleh karena itu manusia harus menjaga, namun demikian tidak selamanya manusia yang telah menjaga kesehatannya akan selalu sehat, tetapi ada kondisi dimana manusia membutuhkan pertolongan oleh tenaga medis untuk menjaga kesehatannya. Tenaga medis yang merupakan tenaga ahli dalam bidang kesehatan memiliki suatu kewajiban untuk melaksanakan tugas sebagai penjaga kesehatan masyarakat. Dalam setiap tindakan medis kepada pasien harus ada persetujuan yang merupakan prinsip dasar dilakukannya layanan medis, oleh karena itu maka dalam penelitian ini memfokuskan peneliti kepada penerapan aspek persetujuan dalam tindakan medis kepada pasien. Penelitian ini bertujuan untuk menganalisis aspek persetujuan dalam tindakan medis yang disebut dengan informed consent yang berdasarkan pada prinsip perjanjian yang di anut oleh hukum positif Indonesia. Penelitian ini menggunakan metode penelitian yuridis normatif yang merupakan kajian regulasi dan kepustakaan yang berkaitan dengan permasalahan yang akan dibahas. Hasil penelitian diharapkan dapat menjadi referensi hukum bagi masyarakat dan juga para tenaga medis sehingga dapat meningkatkan pemahaman dan kesadaran atas tindakan medis yang memiliki resiko tinggi dengan memegang teguh kode etik profesinya dan menjalankan segala prosedur pekerjaan dengan sesuai dengan peraturan yang berlaku.Kata kunci : Persetujuan Tindakan Medis, Informed Consent, Asas Konsensualisme.